2001
DOI: 10.1046/j.1365-3059.2001.00592.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of diagnostic and quantitative PCR for the identification and severity assessment of eyespot and sharp eyespot in winter wheat

Abstract: Diagnostic and quantitative polymerase chain reaction (PCR) provided clarification of the causes of symptoms and the extent of infection by eyespot (Tapesia spp.) and sharp eyespot (Rhizoctonia cerealis) on winter wheat at early growth stages. Disease assessments made before stem extension, when decisions to apply fungicides are usually made, often did not agree with the pathogen diagnoses using PCR, suggesting that such early visual diagnoses may be unreliable. Visual and PCR diagnoses made on stems in summer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 11 publications
1
21
0
Order By: Relevance
“…DNA in rye crop. As has been reported by Turner et al (2001), visual and PCR analyses on wheat stems generally supported each other, but there were often variances in relating disease incidence or the severity of symptoms to the amount of pathogen DNA by regression analyses; however, the relationships between symptoms and eyespot pathogen DNA were less clear on some cultivars. Ray at al.…”
Section: Discussionsupporting
confidence: 67%
“…DNA in rye crop. As has been reported by Turner et al (2001), visual and PCR analyses on wheat stems generally supported each other, but there were often variances in relating disease incidence or the severity of symptoms to the amount of pathogen DNA by regression analyses; however, the relationships between symptoms and eyespot pathogen DNA were less clear on some cultivars. Ray at al.…”
Section: Discussionsupporting
confidence: 67%
“…According to Turner et al (2001), visual and PCR analyses on stems varied in relation to disease incidence or severity of symptoms and to the amount of pathogen DNA. Ramanauskienė et al (2014) have previously reported that stem base and foot rot disease incidence did not correlate with fungal DNA amounts from diseased stems.…”
Section: Resultsmentioning
confidence: 99%
“…The results of 3 years revealed no correlations between these indicators for different agro-ecological zones. The absence of significant relationships suggests that disease development is largely influenced by year and location, probably owing to climatic and agronomic differences [26].…”
Section: Discussionmentioning
confidence: 99%